Maternal and neonatal outcomes of placenta previa and accreta at Assiut women’s health hospital, Egypt - Zakherah, Mahmoud S.; Abdel-Aziz, Mervat; Othman, Essam R.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the current study was to estimate the incidence of placenta previa (PP) and accreta (PA) in the period from January 2015 to December 2016 at Women’s Health Hospital, Assiut University, Egypt and to evaluate the maternal and neonatal outcomes. Methods: The study included all cases of PP with or without suspicion of accreta who were diagnosed preoperatively by ultrasound at Women’s Health Hospital, Assiut University. Maternal and neonatal outcomes were evaluated. All intraoperative and postoperative data were reported. The obtained data was analyzed by means of SPSS software (version 22.0) and p<0.05 was taken as the significant level. Results: Total number of deliveries was 29027 cases. The number of cases of PP was 494 cases making an incidence of 1.7%, among them 95 cases were confirmed during surgery to be accreta (0.33%). Uterine artery ligation was carried out 300 cases (60.7%) of cases while cesarean hysterectomy was performed in 56 cases (11.3%). Bladder injury occurred in 58 cases (11.7%), ureteric injury occurred in 6 cases (1.2%), colon injury occurred in 1case (0.2%) and vascular injury occurred in 2 cases (0.4%). Maternal mortality was 4 cases (0.8%). The mean gestational age was 34.73 ± 2.8 weeks. Also, over the two years there were 148 neonatal cases (29.9%) needed assisted ventilation in the form of ambu bag or endotracheal intubation gestation. NICU admission needed in 109 neonatal cases (22.06%) and neonatal mortality reported in 18 neonates (3.6%). Conclusions: The incidence of both PP and PA is very high in our locality due to increase CS rate.